Foodborne disease in Kenya: County-level cost estimates and the case for greater public investment - Hoffmann, Vivian; Baral, Siddhartha (International Food Policy Research Institute, 2019)
The right to safe food is enshrined in the Kenyan constitution. Through their jurisdiction over matters of agriculture – specifically crop and animal husbandry, abattoirs, and veterinary services – and health, including the licensing and control of undertakings that sell food to the public, county governments in Kenya have a critical role to play in meeting this obligation to their citizens. Food safety has ‘public good’ characteristics and requires sufficient public investment. Appropriate budgetary allocation for food safety investments, requires that county governments understand the current costs of foodborne disease (FBD), as well as the gains they could achieve through improved public capacity to manage food safety risks. However, due to limited availability of data attributing ill-health to specific causes, as well as general under-reporting of health complaints to medical systems, estimates of the health and economic costs of foodborne disease (FBD) in Kenya exist only at the national level. In the context of devolution, the lack of county-specific estimates constitutes a barrier to effective policy-making regarding the control of FBD. In this study, we combine recent national estimates of the health burden attributable to FBD from the World Health Organization (WHO) with county-level data on diarrhea rates to estimate the health and economic burdens of FBD for Murang’a, Laikipia, Nakuru, Nyandarua, and Nairobi counties.